2022
DOI: 10.1186/s13578-022-00759-w
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF1 promotes breast cancer progression by facilitating FOXM1 translation in an m6A-dependent manner

Abstract: Background N6-methyladenosine (m6A) is the most common post-transcriptional modification at the RNA level. However, the exact molecular mechanisms of m6A epigenetic regulation in breast cancer remain largely unknown and need to be fully elucidated. Methods  The integrating bioinformatics analyses were used to screen clinical relevance and dysregulated m6A “reader” protein YTHDF1 in breast cancer from TCGA databases, which was further validated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…Besides, Yu et al analyzed the expression profile of m6A-related regulators acquired from TCGA database, and revealed that upregulated IGF2BP2 in head and neck squamous cell carcinoma (HNSCC) helped stabilize Slug mRNA, thus facilitating MET process and lymphatic metastasis of HNSCC [ 119 ]. Consistently, EMT regulated by m6A has also been observed in other cancers, including GC and breast cancer [ 120 , 121 ]. Taken together, these studies imply that m6A modification may contribute to therapeutic resistance by influencing EMT process.…”
Section: M6a Modification Involved In Regulating Cancer Therapeutic R...supporting
confidence: 61%
“…Besides, Yu et al analyzed the expression profile of m6A-related regulators acquired from TCGA database, and revealed that upregulated IGF2BP2 in head and neck squamous cell carcinoma (HNSCC) helped stabilize Slug mRNA, thus facilitating MET process and lymphatic metastasis of HNSCC [ 119 ]. Consistently, EMT regulated by m6A has also been observed in other cancers, including GC and breast cancer [ 120 , 121 ]. Taken together, these studies imply that m6A modification may contribute to therapeutic resistance by influencing EMT process.…”
Section: M6a Modification Involved In Regulating Cancer Therapeutic R...supporting
confidence: 61%
“…DF1 promotes mRNA translation, DF2 promotes mRNA degradation, and DF3 promotes translation and degradation ( Zaccara and Jaffrey, 2020 ). YTHDF1 and YTHDF3 were also found to overexpress in breast cancer ( Chen et al, 2022 ; Lin et al, 2022 ). IGF2BP 2/3 and YTHDC2 were highly expressed in basal-like breast cancer ( Yang et al, 2020 ).…”
Section: Ribonucleic Acid Modification Regulatory Proteins In Breast ...mentioning
confidence: 99%
“…YTHDF1 and YTHDF3 are highly expressed in BCa patients and with poor prognosis, which can enhance the expression of related genes, such as FOXM1, ST6GALNAC5, GJA1, EGFR, VEGFRA, etc., and promote the metastasis, invasion and angiogenesis of BCa cells ( Chang et al, 2020 ; Chen et al, 2022 ).…”
Section: Part 2: the Role Of M6a Modification In Cancermentioning
confidence: 99%